Automating multistep flow synthesis: approach and challenges in integrating chemistry, machines and logic - Shukla, Chinmay A.; Kulkarni, Amol A. (Beilstein Journal of Organic Chemistry, 2017)
The implementation of automation in the multistep flow synthesis is essential for transforming laboratory-scale chemistry into a reliable industrial process. In this review, we briefly introduce the role of automation based on its application in synthesis viz. auto sampling and inline monitoring, optimization and process control. Subsequently, we have critically reviewed a few multistep flow synthesis and suggested a possible control strategy to be implemented so that it helps to reliably transfer the laboratory-scale synthesis strategy to a pilot scale at its optimum conditions. Due to the vast literature in multistep synthesis, we have classified the literature and have identified the case studies based on few criteria viz. type of reaction, heating methods, processes involving in-line separation units, telescopic synthesis, processes involving in-line quenching and process with the smallest time scale of operation. This classification will cover the broader range in the multistep synthesis literature.
Keywords: automation; control strategy; flow chemistry; in-line monitoring; multistep synthesis optimization

(untitled) - Movsisyan, M.; Delbeke, E. I. P.; Berton, J. K. E. T.; Battilocchio, C.; Ley, S. V.; Stevens, C. V. (Chem. Soc. Rev., 2016)

(untitled) - Kim, H.; Min, K.-I.; Inoue, K.; Im, D. J.; Kim, D.-P.; Yoshida, J.-i. (Science, 2016)

(untitled) - Adamo, A.; Beingessner, R. L.; Behnam, M.; Chen, J.; Jamison, T. F.; Jensen, K. F.; Monbaliu, J.-C. M.; Myerson, A. S.; Revalor, E. M.; Snead, D. R.; Stelzer, T.; Weeranoppanant, N.; et al. (Science, 2016)

(untitled) - Tsubogo, T.; Oyamada, H.; Kobayashi, S. (Nature, 2015)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Adv. Synth. Catal., 2012)

(untitled) - Lovei, K.; Bana, P.; Orkenyi, R.; Turos, G. I.; Eles, J.; Novak, Z.; Faigl, F. (Chim. Oggi, 2016)

(untitled) - Kupracz, L.; Kirschning, A. (Adv. Synth. Catal., 2013)

(untitled) - Heider, P. L.; Born, S. C.; Basak, S.; Benyahia, B.; Lakerveld, R.; Zhang, H.; Hogan, R.; Buchbinder, L.; Wolfe, A.; Mascia, S.; Evans, J. M. B.; Jamison, T. F.; et al. (Org. Process Res. Dev., 2014)

(untitled) - Baxendale, I. R.; Deeley, J.; Griffiths-Jones, C. M.; Ley, S. V.; Saaby, S.; Tranmer, G. K. (Chem. Commun., 2006)

(untitled) - Hartwig, J.; Ceylan, S.; Kupracz, L.; Coutable, L.; Kirschning, A. (Angew. Chem., Int. Ed., 2013)

(untitled) - Murray, P. R. D.; Browne, D. L.; Pastre, J. C.; Butters, C.; Guthrie, D.; Ley, S. V. (Org. Process Res. Dev., 2013)

(untitled) - Guetzoyan, L.; Nikbin, N.; Baxendale, I. R.; Ley, S. V. (Chem. Sci., 2013)

(untitled) - Battilocchio, C.; Deadman, B. J.; Nikbin, N.; Kitching, M. O.; Baxendale, I. R.; Ley, S. V. (Chem. – Eur. J., 2013)

(untitled) - Zhang, P.; Russell, M. G.; Jamison, T. F. (Org. Process Res. Dev., 2014)

(untitled) - Gilmore, K.; Kopetzki, D.; Lee, J. W.; Horváth, Z.; McQuade, D. T.; Seidel-Morgenstern, A.; Seeberger, P. H. (Chem. Commun., 2014)

(untitled) - Martin, A. D.; Siamaki, A. R.; Belecki, K.; Gupton, B. F. (J. Flow Chem., 2015)

(untitled) - Pellegatti, L.; Sedelmeier, J. (Org. Process Res. Dev., 2015)

(untitled) - Lau, S.-H.; Galván, A.; Merchant, R. R.; Battilocchio, C.; Souto, J. A.; Berry, M. B.; Ley, S. V. (Org. Lett., 2015)

(untitled) - Snead, D. R.; Jamison, T. F. (Chem. Sci., 2013)

(untitled) - Correia, C. A.; Gilmore, K.; McQuade, D. T.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2015)

(untitled) - Ghislieri, D.; Gilmore, K.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2015)

(untitled) - Hopkin, M. D.; Baxendale, I. R.; Ley, S. V. (Chem. Commun., 2010)

(untitled) - Borukhova, S.; Noël, T.; Hessel, V. (ChemSusChem, 2016)

(untitled) - Mascia, S.; Heider, P. L.; Zhang, H.; Lakerveld, R.; Benyahia, B.; Barton, P. I.; Braatz, R. D.; Cooney, C. L.; Evans, J. M. B.; Jamison, T. F.; Jensen, K. F.; Myerson, A. S.; et al. (Angew. Chem., Int. Ed., 2013)

(untitled) - Baumann, M.; Baxendale, I. R.; Kirschning, A.; Ley, S. V.; Wegner, J. (Heterocycles, 2011)

(untitled) - Baxendale, I. R.; Ley, S. V.; Mansfield, A. C.; Smith, C. D. (Angew. Chem., Int. Ed., 2009)

(untitled) - Baxendale, I. R.; Schou, S. C.; Sedelmeier, J.; Ley, S. V. (Chem. – Eur. J., 2010)

(untitled) - Petersen, T. P.; Ritzén, A.; Ulven, T. (Org. Lett., 2009)

(untitled) - Adamo, A.; Heider, P. L.; Weeranoppanant, N.; Jensen, K. F. (Ind. Eng. Chem. Res., 2013)

(untitled) - Hartman, R. L.; Naber, J. R.; Buchwald, S. L.; Jensen, K. F. (Angew. Chem., Int. Ed., 2010)

(untitled) - Webb, D.; Jamison, T. F. (Chem. Sci., 2010)

(untitled) - Porta, R.; Benaglia, M.; Puglisi, A. (Org. Process Res. Dev., 2016)

(untitled) - McMullen, J. P.; Jensen, K. F. (Annu. Rev. Anal. Chem., 2010)

(untitled) - Matlin, S. A.; Mehta, G.; Hopf, H.; Krief, A. (Nat. Chem., 2016)

(untitled) - Hayden, E. C. (Nature, 2014)

(untitled) - Peplow, M. (Nature, 2014)

(untitled) - Moore, J. S.; Jensen, K. F. (Angew. Chem., Int. Ed., 2014)

(untitled) - Reizman, B. J.; Jensen, K. F. (Org. Process Res. Dev., 2012)

(untitled) - McMullen, J. P.; Jensen, K. F. (Org. Process Res. Dev., 2010)

(untitled) - McMullen, J. P.; Stone, M. T.; Buchwald, S. L.; Jensen, K. F. (Angew. Chem., Int. Ed., 2010)

(untitled) - Fabry, D. C.; Sugiono, E.; Rueping, M. (React. Chem. Eng., 2016)

(untitled) - Moore, J. S.; Jensen, K. F. (Org. Process Res. Dev., 2012)

(untitled) - Zaborenko, N.; Murphy, E. R.; Kralj, J. G.; Jensen, K. F. (Ind. Eng. Chem. Res., 2010)

(untitled) - Westermann, T.; Mleczko, L. (Org. Process Res. Dev., 2015)

(untitled) - Reizman, B. J.; Wang, Y.-M.; Buchwald, S. L.; Jensen, K. F. (React. Chem. Eng., 2016)

(untitled) - Fitzpatrick, D. E.; Ley, S. V. (React. Chem. Eng., 2016)

(untitled) - Harrison, W. (Drug Discovery Today, 1998)

(untitled) - Hann, M. M.; Oprea, T. I. (Curr. Opin. Chem. Biol., 2004)

Implementing reproducible research - Stodden, V.; Leisch, F.; Peng, R. D. (CRC Press, 2014)

(untitled) - Baker, M. (Nature, 2016)

(untitled) - Jämsä-Jounela, S.-L. (Annu. Rev. Control, 2007)

(untitled) - Stephanopoulos, G. (Comput. Chem. Eng., 1983)

Instrumentation for Process Measurement and Control - Anderson, N. A. (Crc Press, 1997)

Flow measurement handbook: industrial designs, operating principles, performance, and applications - Baker, R. C. (Cambridge University Press, 2005)

Fundamentals of industrial instrumentation and process control - Dunn, W. (McGraw-Hill, 2005)

Instrumentation reference book - Boyes, W. (Butterworth-Heinemann, 2009)

Process modeling, simulation and control for chemical engineers - Luyben, W. L. (McGraw-Hill Higher Education, 1989)

(untitled) - Dunjó, J.; Fthenakis, V.; Vílchez, J. A.; Arnaldos, J. (J. Hazard. Mater., 2010)

(untitled) - Venkatasubramanian, V.; Vaidhyanathan, R. (AIChE J., 1994)

(untitled) - Snead, D. R.; Jamison, T. F. (Angew. Chem., 2015)

F³ Factory website

Texol website

Future Chemistry website

Xytel website

Britest website

BIAZZI website

Snapdragon Chemistry website

Chemical process equipment revised 2E: selection and design - Couper, J. R.; Penney, W. R.; Fair, J. R. (Gulf Professional Publishing, 2009)

Chemical engineering design: principles, practice and economics of plant and process design - Towler, G.; Sinnott, R. K. (Elsevier, 2012)

Perry's chemical engineers' handbook - Perry, R. H.; Green, D. W. (McGraw-Hill Professional, 1999)

(untitled) - Ley, S. V.; Ingham, R. J.; O’Brien, M.; Browne, D. L. (Beilstein J. Org. Chem., 2013)

(untitled) - Saaby, S.; Knudsen, K. R.; Ladlow, M.; Ley, S. V. (Chem. Commun., 2005)

(untitled) - Saleemi, A.; Rielly, C.; Nagy, Z. K. (CrystEngComm, 2012)

(untitled) - Saleemi, A. N.; Rielly, C. D.; Nagy, Z. K. (Cryst. Growth Des., 2012)

(untitled) - Powell, K. A.; Bartolini, G.; Wittering, K. E.; Saleemi, A. N.; Wilson, C. C.; Rielly, C. D.; Nagy, Z. K. (Cryst. Growth Des., 2015)

(untitled) - Powell, K. A.; Saleemi, A. N.; Rielly, C. D.; Nagy, Z. K. (Org. Process Res. Dev., 2016)

(untitled) - Nagy, Z. K.; Braatz, R. D. (Annu. Rev. Chem. Biomol. Eng., 2012)

(untitled) - Braatz, R. D. (Annu. Rev. Control, 2002)

Industrial crystallization process control - Larsen, P. A.; Patience, D. B.; Rawlings, J. B. (IEEE Control Syst. Mag., 2006)

(untitled) - Johnson, M. D.; May, S. A.; Calvin, J. R.; Remacle, J.; Stout, J. R.; Diseroad, W. D.; Zaborenko, N.; Haeberle, B. D.; Sun, W.-M.; Miller, M. T. (Org. Process Res. Dev., 2012)

(untitled) - Johnson, M. D.; May, S. A.; Haeberle, B.; Lambertus, G. R.; Pulley, S. R.; Stout, J. R. (Org. Process Res. Dev., 2016)

(untitled) - Johnson, M. D.; May, S. A.; Calvin, J. R.; Lambertus, G. R.; Kokitkar, P. B.; Landis, C. R.; Jones, B. R.; Abrams, M. L.; Stout, J. R. (Org. Process Res. Dev., 2016)

(untitled) - May, S. A.; Johnson, M. D.; Buser, J. Y.; Campbell, A. N.; Frank, S. A.; Haeberle, B. D.; Hoffman, P. C.; Lambertus, G. R.; McFarland, A. D.; Moher, E. D. (Org. Process Res. Dev., 2016)

(untitled) - Poh, J.-S.; Browne, D. L.; Ley, S. V. (React. Chem. Eng., 2016)

(untitled) - Nagy, K. D.; Shen, B.; Jamison, T. F.; Jensen, K. F. (Org. Process Res. Dev., 2012)

(untitled) - Ranade, V. V.; Sharma, M. K.; Kulkarni, A. A. (Chem. Eng. J., 2015)

(untitled) - Pal, S.; Kulkarni, A. A. (Chem. Eng. Sci., 2016)

(untitled) - Kuhn, S.; Noël, T.; Gu, L.; Heider, P. L.; Jensen, K. F. (Lab Chip, 2011)

(untitled) - Hartman, R. L. (Org. Process Res. Dev., 2012)

(untitled) - Hartman, R. L.; Naber, J. R.; Zaborenko, N.; Buchwald, S. L.; Jensen, K. F. (Org. Process Res. Dev., 2010)

(untitled) - Wong, S.-W.; Changi, S. M.; Shields, R.; Bell, W.; McGarvey, B.; Johnson, M. D.; Sun, W.-M.; Braden, T. M.; Kopach, M. E.; Spencer, R. D.; Flanagan, G.; Murray, M. (Org. Process Res. Dev., 2016)

(untitled) - Chernyak, N.; Buchwald, S. L. (J. Am. Chem. Soc., 2012)

(untitled) - Wedlich, R. C. (Chem. Eng. Prog., 2001)

(untitled) - Shukla, C. A.; Kulkarni, A. A.; Ranade, V. V. (React. Chem. Eng., 2016)

(untitled) - Ley, S. V.; Fitzpatrick, D. E.; Ingham, R. J.; Myers, R. M. (Angew. Chem., Int. Ed., 2015)